Comparative study on cleanup procedures for the determination of organophosphorus pesticides in vegetables - Alvin, Chai Lian Kuet; Lau, Seng (Malaysian Journal of Analytical Sciences, 2008)
A study was carried out to compare the cleanup procedures for the determination of organophosphorus pesticides in vegetables. Eleven organophosphorus pesticides were extracted with acetone and methylene chloride. Extracts were cleanup by solid-phase extraction (SPE) mixed-mode column using quaternary amine and aminopropyl (SAX/NH2) or octadecyl (C18) sorbents. The pesticides were determined by gas chromatography with flame photometric detector. The recovery results obtained from the SPE SAX/NH2 and C18 cleanups in carrot, cucumber and green mustard samples were in the range of 71.0 % to 115 %. Lower recoveries were obtained for polar pesticides, methamidophos and dimethoate. These results were compared to the method currently used in the laboratory which does not include any cleanup.